Avoidance of tracheostomy in sleep apnoea syndrome. - Stradling, JR (1982)
Obstructive sleep apnoea (the Pickwickian syndrome) as a cause of daytime hypersomnolence, intellectual deterioration, and eventual respiratory failure with cor pulmonale and death is well recognized. Tracheostomy may be life saving and is the treatment of choice in some centres, although other methods have been tried with limited success. It is, however, a drastic treatment with medical and psychological implications and if possible should be avoided. We suspect in this patient that the considerably deviated nasal septum, and possibly the tonsils, acted as added upstream resistance. The reduction of this resistance was enough to prevent actual apnoea, although not the snoring. His subsequent weight loss further reduced the tendency to pharyngeal collapse and abolished the snoring. This case suggests that tracheostomy and other complex operations for sleep apnoea may not be necessary.